Aortic aneurysm pressure sensors can be of value in the acute postoperative setting - Gandhi, Ripal T.; Katzen, Barry T.; Tsoukas, Athanassios I.; Geisbüsch, Philipp (Vascular and endovascular surgery, 2011)
Purpose: To report on a case that demonstrates the use and current limits of abdominal aortic pressure sensor devices. Case report: An 83-year-old, high-risk patient underwent endovascular aortic repair (EVAR) of an infrarenal aortic aneurysm (maximum aneurysm diameter: 6.5 cm) with implantation of a pressure sensor device. At the end of the procedure and on the first postoperative day, the sensor detected persistent high pressures in the aneurysm sac, indicating an endoleak that could not be visualized on the intraoperative completion angiography but was confirmed on duplex ultrasound. During repeated angiography (postoperative day 6), again no endoleak could be detected, this time corresponding with the sensor reading that was unfortunately not interrogated again before the reintervention. Conclusion: Pressure sensor devices provide a useful, additional diagnostic tool in detecting and following endoleaks after EVAR and can help guide decisions regarding reinterventions.